High‐Mobility Helical Tellurium Field‐Effect Transistors Enabled by Transfer‐Free, Low‐Temperature Direct Growth. Issue 36 (18th July 2018) - Zhou, Guanyu; Addou, Rafik; Wang, Qingxiao; Honari, Shahin; Cormier, Christopher R.; Cheng, Lanxia; Yue, Ruoyu; Smyth, Christopher M.; Laturia, Akash; Kim, Jiyoung; Vandenberghe, William G.; Kim, Moon J.; et al.
Abstract: The transfer‐free direct growth of high‐performance materials and devices can enable transformative new technologies. Here, room‐temperature field‐effect hole mobilities as high as 707 cm 2 V −1 s −1 are reported, achieved using transfer‐free, low‐temperature (≤120 °C) direct growth of helical tellurium (Te) nanostructure devices on SiO2 /Si. The Te nanostructures exhibit significantly higher device performance than other low‐temperature grown semiconductors, and it is demonstrated that through careful control of the growth process, high‐performance Te can be grown on other technologically relevant substrates including flexible plastics like polyethylene terephthalate and graphene in addition to amorphous oxides like SiO2 /Si and HfO2 . The morphology of the Te films can be tailored by the growth temperature, and different carrier scattering mechanisms are identified for films with different morphologies. The transfer‐free direct growth of high‐mobility Te devices can enable major technological breakthroughs, as the low‐temperature growth and fabrication is compatible with the severe thermal budget constraints of emerging applications. For example, vertical integration of novel devices atop a silicon complementary metal oxide semiconductor platform (thermal budget <450 °C) has been theoretically shown to provide a 10× systems level performance improvement, while flexible and wearable electronics (thermal budget <200 °C) can revolutionize defense and medical applications. Abstract : High‐quality helical tellurium (Te) is directly grown on amorphous dielectrics and flexible substrates with growth and device fabrication performed at 120 °C and lower. Back‐gate field‐effect transistors fabricated from needle‐like Te structures directly grown on SiO2 /Si show a room‐temperature hole mobility as high as 707 cm 2 V −1 s −1, which can enable transformative new technologies.